2022
DOI: 10.3389/fgene.2021.765985
|View full text |Cite
|
Sign up to set email alerts
|

Protein Network Analysis of Whole Exome Sequencing of Severe Preeclampsia

Abstract: Preeclampsia is a hypertensive disorder of pregnancy, which complicates up to 15% of US deliveries. It is an idiopathic disorder associated with several different phenotypes. We sought to determine if the genetic architecture of preeclampsia can be described by clusters of patients with variants in genes in shared protein interaction networks. We performed a case-control study using whole exome sequencing on early onset preeclamptic mothers with severe clinical features and control mothers with uncomplicated p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(79 reference statements)
0
4
2
Order By: Relevance
“…To the best of our knowledge, among the top 8 proteins in our prediction model, only QSOX1, a marker of cellular growth and extracellular matrix remodeling, has previously been reported as having a role in pregnancy. 26,27 In those studies, higher levels of QSOX1 were found to be associated with preeclampsia, yet here we found higher levels of QSOX1 to be associated with lower risk of HDP. This finding is not dissimilar to that of sFlt-1, which has been shown to be elevated in the setting of clinically evident preeclampsia but has an inverse association with the subsequent development of preeclampsia when assayed early in pregnancy.…”
Section: Discussioncontrasting
confidence: 61%
“…To the best of our knowledge, among the top 8 proteins in our prediction model, only QSOX1, a marker of cellular growth and extracellular matrix remodeling, has previously been reported as having a role in pregnancy. 26,27 In those studies, higher levels of QSOX1 were found to be associated with preeclampsia, yet here we found higher levels of QSOX1 to be associated with lower risk of HDP. This finding is not dissimilar to that of sFlt-1, which has been shown to be elevated in the setting of clinically evident preeclampsia but has an inverse association with the subsequent development of preeclampsia when assayed early in pregnancy.…”
Section: Discussioncontrasting
confidence: 61%
“…Demonstrating VGC's capabilities, we present an example using whole exome sequencing data from preeclamptic patients and term mothers. The dataset includes 143 samples: 61 early onset severe preeclamptic cases and 82 term mother controls [16]. Through VGC, we offer a detailed analysis of this dataset, emphasizing major trends, statistical findings, and key outcomes aligned with our research goals.…”
Section: Resultsmentioning
confidence: 99%
“…Fibronectin 1 (FN1) is a glycoprotein that is involved in cell adhesion and cell spreading and is widely distributed in healthy membranes, vascular structures, and smooth muscle cell layers. [25][26][27] The plasma levels of FN1, which may be the best marker for vascular endothelial injury during PE, are increased in patients with PE. [28] Multiple studies have shown that FN1 is related to the pathogenesis of PE, and FN1 can be used as a potential marker in the diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%